Factors That Inhibit Tourism Development: A Case Study of Ababa (Festival) Religio- Cultural Carnival in Oron - Okon, Anthony Ben (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2018)
Religious tourism is as old as religion itself and consequently, it is the oldest form of tourism in the world. Most religions have holy places that people visit from time to time for several reasons. This work examines the Ababa carnival which involves faith- activities, but in a heightened form. It involves pilgrimages to the Ababa holy shrine in Esin Ufot Eyo-Abasi in Oron. This work identifies as a problem, the lack of basic infrastructures and non-patriotic and neglecting attitudes of Nigerians towards their indigenous religious tourism development, as they are so much involved in faith-based activities and travels to Israel, Mecca, Rome among several others. It adopts the Phenomenological method in a Culture Area of Oron. As primary research, it will rely on oral interviews and secondary materials from the libraries and the internet. The findings indicate that the positive effects of indigenous faith-based religious tourism such as Ababa are yet to be used in developing Oron and Nigeria as found in other parts of the world such as Israel, Saudi Arabia, and Italy. This work concludes that Traditional Religious tourism can be used as a tool for the National Development and unity of Nigeria. As a recommendation it calls on the government who sponsors individuals and particular religious groups on pilgrimages, to divert such funds and invest in infrastructural development in Oron to attract tourists to the area and as well develop traditional religious tourism of Nigeria, as this will reduce poverty and create employment opportunities.